EXISTENTIAL-PHENOMENOLOGICAL SUPPORT GROUPS ADDRESSED TO PARENTS OF CHILDRENS WITH VARIOUS NEURODEVELOPMENTAL DISORDERS: PRINCIPLES, MODELS, IMPLEMENTATION AND FUNCTIONING FEATURES - GRUIA, Ioan Emanuel (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Existential-Phenomenological Support Groups Addressed to Parents of Childrens with Various Neurodevelopmental Disorders: Principles, Models, Implementation and Functioning Features. This article aims to present the principles, techniques and models of existential-phenomenological philosophical counseling, as well as the way in which philosophical practice can be used to support discussions within support groups addressed to parents of children with disabilities. A model of philosophical existential-phenomenological group counseling will also be proposed, addressing the parents of children diagnosed with autistic spectrum disorder. The phases of the group counseling process as well as individual counseling through phenomenology will be reproduced in this article, which will also propose possible themes that discussions in workshops with parents of children with disabilities can be based on.